Analysis of AVPR1A, thermal and pressure pain thresholds, and stress in sickle cell disease - Powell-Roach, Keesha L.; Yao, Yingwei; Cao, Xueyuan; Chamala, Srikar; Wallace, Margaret R.; Cruz-Almeida, Yenisel; Molokie, Robert E.; Wang, Zaijie Jim; Wilkie, Diana J. (Frontiers in Pain Research, 2023)
Aim: In patients with sickle cell disease (SCD), negative physical and emotional experiences result from intense chronic and acute pain episodes, but factors underlying these, and their interactions, are not well understood. The arginine vasopressin receptor 1a gene (AVPR1A) single nucleotide polymorphism rs10877969 has been previously associated with aspects of acute pain and stress related pain. In this study, we tested for associations between this SNP, thermal and pressure pain thresholds, clinical pain, and stress in people with SCD. Methods: 150 adults enrolled with SCD completed pain intensity measures (Average Pain Intensity, API) and the Perceived Stress Questionnaire (PSQ). Thermal and pressure pain threshold data were available from quantitative sensory testing (QST), and rs10877969 genotypes were obtained. Results: In models adjusted for age and gender, between rs10877969 genotypes, we observed no significant differences in thermal (cold, p=0.66; heat, p=0.91) and mechanical (pressure, p=0.33) pain thresholds. The association of rs10877969 with API (p=0.09) was borderline, but non-significant with PSQ (p=0.51). The correlation between clinical pain and environmental stress was significant, r=0.18, p=0.024, however, the interaction of genotype and PSQ was not significant (p=0.63). Conclusion: Clinical and experimental pain were not significantly associated with the rs10877969 genotype. The rs10877969 genotype did not moderate the correlation between environmental stress and clinical pain in this population. However, a trend toward a protective T allele effect on average pain rating in SCD warrants future exploration of this SNP/gene in SCD.